Tackling bribery in accessing kenyan citizenship: towards implementing and enforcing anti-corruption measures - Lugulu, Julie (Journal of Anti-Corruption Law, 2023)
Every Kenyan citizen has the right to acquire civic identification documents pursuant to article12 of the Kenyan Constitution, 2010. This right allows Kenyans to apply for birth certificates, national identification documents and passports. These identification documents are crucial in proving that a person has a genuine link with Kenya which in turn unlocks their enjoyment of socioeconomic and political rights. Conversely, without identity documentation, a person’s access to socioeconomic and political rights is limited. Consequently, one may face challenges in accessing education, adequate healthcare, opening a bank account, travelling abroad, owning property, voting and vying for political posts, among others. The Department of Civil Registration Services has the mandate of registering births and deaths, while the National Registration Bureau is tasked with providing national identification documents. Reports conducted by the Ethics and Anti-Corruption Commission (EACC) and the Kenya National Commission on Human Rights (KNCHR) indicate that some applicants seeking civic identification documents were asked for bribes by some registration officials in order to acquire the documentation or expedite the process. Kenya has made positive strides towards combating corruption through enacting extensive domestic anti-corruption legislation and ratifying international and regional legislation on anti-corruption. This paper argues that, successful implementation and enforcement of the existing anti-corruption laws by anti- corruption agencies will play a major role in curbing bribery that is experienced while accessing identification documents in Kenya.